2012
DOI: 10.4103/0970-9185.101916
|View full text |Cite
|
Sign up to set email alerts
|

A randomized prospective study of desflurane versus isoflurane in minimal flow anesthesia using "equilibration time" as the change-over point to minimal flow

Abstract: Background:In the administration of minimal flow anesthesia, traditionally a fixed time period of high flow has been used before changing over to minimal flow. However, newer studies have used “equilibration time” of a volatile anesthetic agent as the change-over point.Materials and Methods:A randomized prospective study was conducted on 60 patients, who were divided into two groups of 30 patients each. Two volatile inhalational anesthetic agents were compared. Group I received desflurane (n = 30) and group II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…This method is an effective alternative to the use of inhalational agent at this period of time. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method is an effective alternative to the use of inhalational agent at this period of time. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…Mean equilibration time obtained for desflurane and isoflurane were 4.96 ± 1.60 min and 16.96 ± 9.64 min and was statistically significant ( P < 0.001). [ 3 ] Although in these studies, sevoflurane was not studied, isoflurane and desflurane were compared and time taken to achieve equilibration time in these studies was more with isoflurane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies done with LMA and minimal flow anesthesia have concluded that drowsiness was more with isoflurane than other inhalational agents. [ 21 22 ] In our study, we did not monitor sedation score. Patients were monitored only with modified Aldrete scale which showed no difference among the groups.…”
Section: Discussionmentioning
confidence: 96%
“…The time to shift towards low flow also needs special attention in the practice of LFA. Use of equilibration time of the volatile anesthetic agent as the change-over point can help the anesthesiologists in the of use minimal flow anesthesia, in a more efficient way 10. A study using Smart Anesthesia Manager TM and Anesthesia Information Management System to notify the anesthesia team if FGF exceeds 1 L/min found that real-time notification is an effective way to reduce excess FGFs 11.…”
Section: Discussionmentioning
confidence: 99%